Unlocking employee potential through motivation workplace dynamics and incentives: A holistic approach to driving productivity - Ibrahim, Irmohizam; Abiddin, Norhasni Zainal (Edelweiss Applied Science and Technology, 2024)
Modern workplaces have evolved so much that it requires a change in how companies think of employee motivation and productivity. The study aimed to finding out the association between employee motivation and incentive systems to formulate a model that will guide on how best overall organizational productivity could be boosted. It also offers insights based on research proven strategies for building the type of workplace that will motivate employees. The research used a quantitative approach with cross-sectional survey design. Three hundred and fifty individuals were surveyed from 10 organizations across a range of industries, organizational levels. Stratified random sampling approach was used to ensure that all age groups as well as different generational and working models were represented in sample across cultures. Structural equation modelling (SEM) by means of AMOS 26 was applied and an analysis of the results revealed some important paths for critical organisational variables. The findings found was motivation, with high relationships to the workplace environment (β = 0.42), communication (β = 0.55) and incentives (p < Workplace environment was empirically shown to have a positive but weak effect on productivity (β =0.13), and the strong relationship with communication (β = 0.80). The proposed model shows a good fit in multiple indices: GFI (0.852), CFI (0.913), TLI (0.900) and RMSEA 90(74)], thereby validating the structure of the framework along with all its measured variables. These results suggest that organizations need to take a comprehensive view when looking at ways to motive and increase productivity of employees by being able understand the complex interrelations among work behaviors. This has operational implications for leaders and human resource professionals who seek a combined impact by aligning work designing, communication systems, incentive design structures and cultural integration strategies.